PENGARUH EARNING PER SHARE (EPS) DAN PRICE BOOK VALUE (PBV) TERHADAP HARGA SAHAM PADA INDUSTRI RETAIL YANG TERDAFTAR DI BEI PERIODE 2013-2016 - Hana Tamara Putri (Universitas Batanghari, 2018)
The purpose of this studyis to find out how the influence of earnings per share (EPS) and price book value (PBV) simultaneously and parcial to stock prices in retail industry listed on the Stock Exchange Indonesia period 2013-2016. The ojek this analysis is the retail industry listed on the stock exchange indonesia period 2013-2016. Sampel used in this research is as many as 8 retail industry listed on the Stock Exchange Indonesia period 2013-2016. The method used is qualitative and quantitative method. . The analytical tool used in this research is multiple linear regression analysis, the classical assumption test (normality, multicolinearity, hetoroscedasicity, and autocorrelation) and coefficient of determination. Based on the results of multiple linear regression analysis showed the equation Log Y= 2.244 + Log 0,528EPS Log 0,018PBV + e , with F test value of 5,153. Value t test for earning per share (EPS) of 3,159 and the value of T test for price book value (PBV) of 0,113. Rated R Square 26,2%, while the remaining 73,8% explained other factors beyond the study models. And the R value of 0,512. The conclusion of this research indicates that simultaneously independent variable earnings per share (EPS) and price book value (PBV) have an effect on stock price variable. The parcial price (PBV) has no significant effect on stock price dependent and earnings per share (EPS) have a significant effect on stock price variables.